SMEs and strategic alliances - Farizah Fasalul Rahman (2008)
This study attempts to understand why some SMEs failed in their effort to regionalise while others succeed. Hence, this study examines the partner selection process and the involvement of social processes during this partner selection stage, as well as the roles that it play in the formation of strategic alliance